Concept of green dentistry in Serbia - Zdravković Dejan; Jovanović Milica; Milojević-Šamanović Anđela; Papić Mirjana; Papić Miloš; Milosavljević Marko; Obradović-Đuričić Kosovka (Srpski Arhiv za Celokupno Lekarstvo)
Introduction/Objective. Green dentistry as a term has been introduced into dental practice in Serbia in recent years. Minimal amount of research on the topic of medical waste disposal in health care institutions is available at the moment. The aim of this research is to determine how familiar the professional public as well as dental students are with this term and whether they apply the recommended environmental protection measures in their daily clinical work. Methods. The study was conducted in the form of a survey that referred to the attitude of the professional public regarding environmentally friendly dental practice, in the period from June 1, 2022 until November 1, 2022. The survey includes demographic information, as well as 21 questions related to awareness and application of green dentistry in daily clinical practice. Results. Results indicate a very low level of information among the professional public regarding the mentioned concept, where as much as 36% of the total number of respondents do not have any information about green dentistry (n = 45) and only 6% (n = 8) are fully informed about the given concept. Conclusion. On the basis of the obtained results, it can be concluded that the professional public’s attitude towards green dentistry is such that its application is expected to reduce the consumption of available resources, as well as to improve the environment.